2013
DOI: 10.47338/jns.v2.51
|View full text |Cite
|
Sign up to set email alerts
|

Single Stage Transanal Pull-Through for Hirschsprung’s Disease in Neonates: Our Early Experience

Abstract: Objective: Hirschsprung’s disease is one of the common causes of intestinal obstruction in neonates. Transanal endorectal pull-through represents the latest development in the concept of the minimally invasive surgery for Hirschsprung’s disease. In this study, we present our early experience with single stage transanal pull through in neonates. Design: Retrospective study of neonates with single stage transanal pull-through done for Hirschsprung’s disease in our institute from January 2011 to January 2013. Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
2
5
0
Order By: Relevance
“…The conventional three stages procedure of HD by Swenson, Duhamel, and Soave had been substituted in the last two decades by the one stage TEPT and starts to gain popularity among pediatric surgeons due to its feasibility and less complication with results equal if not better than the traditional three stage procedures (6).In our study TEPT was carried on 11 patients, their ages were ranging from 1 month to 12 years; with a mean of (33.7±43.4 months), which reflects a wide range of ages at the time of pullthrough which refers to the feasibility of TEPT during and beyond the neonatal period, a fact that was documented by other studies done by Langer et al (7), and Bahatial et al (8). In the present series the male: female ratio was 4.5:1 which is differs from Ortiz-Rubio et al( 9) who described a male: female ratio of 1.8 : 1 but it agrees with the general concept and Langer et al (7) who described a ratio of 4 : 1 .…”
Section: Discussionsupporting
confidence: 68%
“…The conventional three stages procedure of HD by Swenson, Duhamel, and Soave had been substituted in the last two decades by the one stage TEPT and starts to gain popularity among pediatric surgeons due to its feasibility and less complication with results equal if not better than the traditional three stage procedures (6).In our study TEPT was carried on 11 patients, their ages were ranging from 1 month to 12 years; with a mean of (33.7±43.4 months), which reflects a wide range of ages at the time of pullthrough which refers to the feasibility of TEPT during and beyond the neonatal period, a fact that was documented by other studies done by Langer et al (7), and Bahatial et al (8). In the present series the male: female ratio was 4.5:1 which is differs from Ortiz-Rubio et al( 9) who described a male: female ratio of 1.8 : 1 but it agrees with the general concept and Langer et al (7) who described a ratio of 4 : 1 .…”
Section: Discussionsupporting
confidence: 68%
“…This complication is more frequent for patients treated with TAPT during the neonatal period, according to a meta-analysis conducted by Westfal et al [14] which can be explained by increased susceptibility of newborns to infections. [15] This complication was neither reported in the study conducted by Bhatia et al [8] nor by Hassan et al [4] and reported in only one patient by Ali. [16] Post-operative enterocolitis is considered one of the main complications of patients with HD before and after definitive treatment.…”
Section: Discussionmentioning
confidence: 88%
“…A large number of pediatric surgeons preferred the singlestage procedure at an early age. [8] The primary TAPT for HD has the advantage of avoiding the colostomy and its related complications including its social stigma. The aim of our study was to evaluate the feasibility, safety, and outcomes of TAPT during the neonatal period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anastomotic leaks or strictures and the development of postoperative bowel obstruction secondary to adhesions increase the relative risk and subsequent enterocolitis by approximately 3-fold. Long seromuscular cuffs and high coloanal anastomoses are associated with an increased risk of postoperative enterocolitis [46]. Perianal rash or skin excoriation is common after pull-through surgery, especially among children who have had a stoma before pull-through, long segment colon or total colonic aganglionosis, and patients who have undergone surgery as neonates [22].…”
Section: International Journal Of Scientific Advances Issn: 2708-7972mentioning
confidence: 99%